0370 Patient-reported Sleep Onset and Sleep Maintenance: Pooled Analyses of Lemborexant Phase 3 Studies. (12th April 2019) - Zee, Phyllis C; Murphy, Patricia; Yardley, Jane; Pinner, Kate; Kumar, Dinesh; Perdomo, Carlos; Moline, Margaret
Abstract: Introduction: Current insomnia treatments, such as the GABA-ergic, non-benzodiazepine sedative-hypnotics, may not adequately treat both sleep onset and sleep maintenance symptoms, and are associated with risk of falls, tolerance/dependence, and abuse potential, among others. Drugs targeting the orexin system, like lemborexant (LEM), may dampen wakefulness, facilitating sleep with fewer potential adverse consequences. These analyses are from 1-month of pooled data from 2 Phase 3 studies in adult and older subjects with DSM-5 insomnia disorder. Methods: SUNRISE-1 was a 1-month, double-blind, randomized, placebo (PBO)- and active-controlled, parallel-group study in 1006 subjects (age ≥55y). Subjects were randomized to PBO, LEM 5mg (LEM5), LEM 10mg (LEM10) or zolpidem tartrate extended-release (ZOL; 6.25mg; not reported). SUNRISE-2 was a 12-month (6-month PBO-controlled, 6-month active treatment), double-blind study in 949 subjects (age ≥18y) randomized to PBO, LEM5 or LEM10. Subjects completed a daily electronic diary regarding time to fall asleep (sSOL), wake after sleep onset (sWASO), time in bed, among others. Both studies included a 2-week placebo run-in. Data from the first month of treatment were pooled for sSOL, subjective sleep efficiency (sSE) and sWASO. ZOL was not studied in SUNRISE-2; data were not pooled. Data were analyzed by mixed effect model repeated measurement. Results: Subjects analyzed were: PBO 527, LEM5 582, LEM10 584. Reduction in sSOL was statistically greater for both doses of LEM versus PBO for the first 7 days of treatment and end of Month 1 (all comparisons P <0.0001). Both doses, versus PBO, significantly increased sSE ( P <0.0001 both time points) and reduced sWASO (P<0.001 first 7 days [both doses]; P<0.05 [LEM5] and P<0.001 [LEM10] at Month 1). Average values on sleep maintenance endpoints showed that subjects taking LEM obtained >1 hour of additional sleep per night. LEM was well-tolerated, with most adverse events (AEs) being mild to moderate in severity and low rates of serious AEs. Conclusion: LEM demonstrates efficacy on sleep onset and sleep maintenance variables in a broad age range of subjects with insomnia disorder, with good tolerability. Support (If Any): Eisai, Inc., Purdue Pharma L.P.